Manufacturing method for food and beverage can lids
By using an aluminum alloy with specific composition ranges and a unique score forming blade, the challenges of using recycled aluminum UBC in can lids are addressed, resulting in enhanced strength and corrosion resistance while reducing environmental impact.
Patent Information
- Application Number
- JP2023095462
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-25
- Filing Date
- 2023-06-09
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-11-25
AI Technical Summary
The use of recycled aluminum alloy from used beverage cans (UBC) in can lids is challenging due to its composition, which has a high Mn content and low Mg content, leading to reduced strength and increased risk of unintended breakage and corrosion.
The method involves forming the ends and tabs of the can lid from an aluminum alloy with specific composition ranges (Mn: 0.5-1.4%, Mg: 2.0-4.5%, Si: 0.6%, Fe: 0.8%, Cu: 0.25%, Cr: 0.10%, Zn: 0.25%, Ti: 0.10%) and using a score forming blade with a unique shape to enhance score strength and prevent microcracks.
This approach enables the production of can lids with excellent pressure resistance and opening properties, even when using recycled aluminum UBC material, while reducing the need for new aluminum and minimizing carbon dioxide emissions.
Smart Images

Figure 0007662919000012 
Figure 0007662919000013 
Figure 0007662919000014
Abstract
Description
[Technical Field]
[0001] The present invention relates to an aluminum alloy can lid consisting of an end and a tab for tearing open a score formed in the end. More specifically, the present invention relates to a method for manufacturing a can lid for food and beverages that has the performance required for the end and tab while using recycled material made from aluminum cans after their contents have been consumed. [Background technology]
[0002] Food and beverage cans, which are made by attaching an aluminum can lid to a can body made of a metal such as aluminum or steel, are widely used as cans for filling foods and beverages such as beer and soft drinks. Such aluminum can lids generally consist of an end and a tab for tearing a score formed in the end to form an opening defined by the score. Materials used for can ends must have strength, formability, corrosion resistance, etc. That is, the ends must have excellent pressure resistance so that the can ends do not deform, even in the case of positively pressurized cans containing carbonated beverages or negatively pressurized cans where the pressure is reduced due to a drop in temperature caused by filling the contents at high temperature, and must have sufficient toughness to prevent the score from breaking unintentionally. On the other hand, the tabs must have sufficient breaking strength and toughness to prevent bending or tearing when forming the opening.
[0003] As an aluminum alloy used for can lids, for example, Patent Document 1 listed below proposes a beryllium-free aluminum-magnesium alloy that is inhibited from being oxidized by melting, which contains 0.8 to 15 mass% of Mg and 0.2 to 0.6 mass% of Fe, with the total content of Al and Mg being 90 mass% or more, and the content of P as an impurity being 0.001 mass% or less. Further, Patent Document 2 listed below discloses a cold-rolled sheet material having a thickness of 0.22 to 0.25 mm, which is made of an aluminum alloy containing, on a mass basis, 0.80 to 1.50% Mg, 0.80 to 1.20% Mn, 0.40 to 0.60% Fe, 0.20 to 0.40% Si, and 0.15 to 0.25% Cu, and which satisfies the content relations of Mn / Fe=1.5 to 2.5 and Mg / Mn≧1.0, with the remainder being aluminum and unavoidable impurities, The proposed aluminum alloy sheet for negative pressure can ends is characterized in that one or both sides thereof are coated with an organic resin film, and that after paint baking, the 45° earing is 1.5 to 3.0%, the 0-180° earing is 1.0 to 2.5%, and the formula: -0.6%≦(45° earing)-(0-180° earing)≦1.5% is satisfied, and further the tensile strength in the direction 0° to the rolling direction is 270 to 300 MPa and the proof stress is 240 to 270 MPa. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5920705 [Patent Document 2] Patent No. 5898426 Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, nearly 100% of used beverage cans (hereinafter sometimes referred to as "UBC") after their contents have been consumed are collected, and in the case of aluminum beverage cans, they are recycled into aluminum bullion. While 3000-series aluminum alloys with a high Mn content are generally used for can bodies, 5000-series aluminum alloys with a high Mg content, which are superior in strength to 3000-series aluminum alloys, are used for can ends (ends and tabs) from the viewpoints of strength, formability, corrosion resistance, etc. Therefore, recycled aluminum alloys made from UBC have a composition similar to that of 3000-series aluminum alloys, which account for a large proportion of the overall weight of aluminum beverage cans, and have a higher Mn content and lower Mg content than 5000-series aluminum alloys, making them difficult to use for can ends, and virgin aluminum ingots have had to be used for can ends. However, producing virgin aluminum ingots requires a large amount of electricity, which results in large carbon dioxide emissions, and from the perspective of the environmental impact, there is a demand for the use of recycled materials for can ends as well.
[0006] Furthermore, in aluminum alloys with a high Mn content that use recycled aluminum alloys composed of UBC, the strength of the score formed in the end decreases due to an increase in Al-Fe-Mn-Si crystals. This can lead to unintended fracture of the score when dropped or impacted, resulting in leakage of contents. It has also been found that microcracks occur in the organic coating on the inner surface of the score (the inner surface of the end) and on the rivet forming portion for attaching the tab, which can lead to metal exposure and corrosion of the end over time during storage. Furthermore, aluminum alloys with an increased amount of Al-Fe-Mn-Si crystals have reduced toughness, making them prone to cracking. This can lead to derailment and fracture when breaking the score to form an opening. In addition, the tab attached to the end is generally made of a thin plate for ease of forming an opening and for the strength of the tab, and the end is formed by bending the gripping part for the fingers and curling the other parts. In this case, if an aluminum alloy with an increased amount of Al-Fe-Mn-Si crystallized matter is used, there is a risk of the tab breaking or cracks occurring on the metal surface of the processed part.
[0007] Therefore, an object of the present invention is to provide a can lid having an end and / or a tab that has the pressure resistance and other performance required for a can lid, even if it contains a recycled aluminum alloy made from aluminum UBC. Another object of the present invention is to provide a can lid having an end and / or tab that has high score strength, effectively prevents leakage of contents due to unintended rupture of the score, and effectively prevents microcracks in the organic coating due to score processing, even when formed from a material containing a recycled aluminum alloy made from aluminum UBC that has a high Mn content and a large amount of Al-Fe-Mn-Si crystallized matter, and is also effectively prevented from rupturing at locations other than the score. [Means for solving the problem]
[0008] According to the present invention, there is provided a method for manufacturing a can lid for food or beverages, the can lid comprising an end and a tab, the end being formed with a breakable score defining a planned opening portion, and the tab being attached with a rivet, the method comprising the steps of: the end and / or tab is made of an aluminum alloy containing 0.5 to 1.4 mass% of Mn, 2.0 to 4.5 mass% of Mg, 0.6 mass% or less of Si, 0.8 mass% or less of Fe, 0.25 mass% or less of Cu, 0.10 mass% or less of Cr, 0.25 mass% or less of Zn, and 0.10 mass% or less of Ti; The method for manufacturing a can lid for food or beverage is characterized in that the score forming blade used to form the breakable score comprises, in a vertical cross section in the width direction of the score forming blade, opposing sloping sides whose blade width decreases toward the tip, and a tip portion located at the lower end of the sloping sides, and the width of the tip portion has at least a portion that is 65% or less of the width of an imaginary tip surface defined by an imaginary extension line of the sloping sides and an imaginary extension line passing through the center of the tip portion, and a flat portion is formed in the center of the tip portion, and the width of the flat portion is 65% or less of the width of the imaginary tip surface.
[0009] In the method for producing a food and beverage can lid of the present invention, (1) Both sides of the tip are continuous with the inclined side surfaces and curved surfaces; (2) The breakable score has opposing inclined surfaces and a bottom surface in a vertical cross section in the width direction of the score, the score width decreasing downward, and the width of the bottom surface has at least a portion that is 65% or less of the width of an imaginary bottom surface defined by an imaginary extension line of the inclined surfaces and an imaginary extension line passing through the center of the bottom surface. (3) A flat portion is formed in the center of the bottom surface, and the width of the flat portion is 65% or less of the width of the imaginary bottom surface. (4) The width defined by an imaginary extension line of the inclined surface and an imaginary extension line passing through the center of the bottom surface is 15 to 40 μm. (5) The score angle formed by the inclined surface is 40 to 60 degrees. (6) The breakable score is a main score, and auxiliary scores are provided adjacent to the main score and positioned inward from the main score, and in a cross section perpendicular to the width direction of the score, the amount of metal rejected by the auxiliary score machining (S0) is 25% or more of the amount of metal rejected by the main score machining (S1). (7) The above The breakable score is the main score, and the The main score has a high score remaining thickness portion in which the score remaining thickness relative to the virtual thickness in the case where no score is formed in the score processing portion is greater than the main score remaining thickness ratio and is 85% or less. (8) The breakable score is a main score, and an auxiliary score is provided adjacent to the main score and located inward from the main score, and an anti-blowout score is formed adjacent to the main score near the initial opening portion of the main score, and the remaining score thickness of the anti-blowout score is 70 to 90% of the original plate thickness. (9) A rivet forming portion for attaching a tab is formed at the end, and the processing rate of the rivet forming portion relative to the original plate thickness at the center is 70% or less of the original plate thickness. (10) The height of the rivet forming portion relative to the inner diameter of the side wall portion of the rivet forming portion of the end surface The proportion of the coining processing area is 40 to 95%. (11) In the finger loop portion of the tab, the ratio of the thickness of the finger loop portion to the original thickness (thickness of the finger loop portion / original thickness) is 2 or more and is equal to or less than the ratio of the thickness of the curl portion of the tab to the original thickness (thickness of the curl portion / original thickness), is preferred. [Effects of the Invention]
[0010] According to the food and beverage can lid of the present invention, even when a recycled aluminum UBC is used, the main components of the alloy elements are within the above ranges, so that an end with excellent pressure resistance and a tab with excellent breakage resistance can be obtained, which makes it possible to reduce the amount of virgin aluminum used, which emits a large amount of carbon dioxide. Furthermore, in the food and beverage can lid of the present invention, even if the Mg content in the recycled aluminum UBC material is in a range different from that of the 5000 series aluminum alloy, strength can be obtained due to the Mn contained in the recycled material, and by specifying the original plate thickness (non-processed portion) of the end and the remaining thickness in the initial opening portion of the score processed portion, it is possible to provide a can lid that does not impair the performance required of a can lid, such as pressure resistance strength and openability.
[0011] In the present invention, by improving the configuration (shape, dimensions, etc.) of the breakable score (main score) formed in the end, even ends made of recycled aluminum alloys derived from aluminum UBCs, which have an increased concentration of Al-Fe-Mn-Si crystals, have high score strength and are effectively prevented from unintended fracture of the score, even when subjected to a drop impact. Furthermore, the occurrence of microcracks in the organic coating on the backside of the score (inner surface of the end) and on the rivet top surface is effectively prevented, providing an end with excellent corrosion resistance. Furthermore, when the score breaks, there is no breakage (derailment) in areas other than the score, and no so-called pop missile phenomenon occurs when the package is initially opened, resulting in excellent openability. Furthermore, by improving the thickness of the curled portion and the finger loop portion formed by bending as described above for the tab attached to the score, it is possible to maintain excellent opening properties while effectively preventing cracks from occurring on the metal surface of the tab and scratches on the rivet when attaching the tab to the end.
[0012] Furthermore, according to the manufacturing method of the end of the present invention, even when using an aluminum UBC that has a high Mn content and is prone to increase Al-Fe-Mn-Si-based crystallized particles, it is possible to form a score with the above-described high score strength. [Brief explanation of the drawings]
[0013] [Figure 1] 1A and 1B are diagrams showing an example of a can lid of the present invention, in which (A) is a plan view and (B) is a cross-sectional view. [Figure 2] FIG. 10 is a partially enlarged cross-sectional view illustrating the score processing portion of the end. [Figure 3] 10 is a diagram for explaining the score processing portion of the end, and is a partially enlarged cross-sectional view of the axial cross section in the width direction of the score. FIG. [Figure 4] FIG. 10 is a partially enlarged cross-sectional view illustrating the amount of metal displacement of the main score and the auxiliary score. [Figure 5] FIG. 2 is a partially enlarged cross-sectional view showing an axial cross-section in the length direction of the score. [Figure 6] FIG. 10 is a partially enlarged plan view illustrating a score formed in the vicinity of a tab attachment portion by a rivet. [Figure 7] FIG. 4 is an enlarged cross-sectional view of a rivet forming portion. [Figure 8] 10 is a cross-sectional photograph of a tab attachment portion. [Figure 9] 1A and 1B are diagrams showing an example of a tab used in the present invention, in which (A) is a plan view and (B) is a cross-sectional view. [Figure 10] 1 is a diagram for explaining a score forming blade used in the manufacturing method of an end cap of the present invention, and is an enlarged cross-sectional view of a width direction cross section of the score forming blade. FIG. DETAILED DESCRIPTION OF THE INVENTION
[0014] (aluminum alloy) An important feature of the can lid for food and beverages of the present invention is that the aluminum alloy constituting the end and / or tab of the can lid contains Mn: 0.5 to 1.4 mass%, Mg: 2.0 to 4.5 mass%, Si: 0.6 mass% or less, Fe: 0.8 mass% or less, Cr: 0.10 mass% or less, Zn: 0.25 mass% or less, Ti: 0.10 mass% or less, and Cu: 0.25 mass% or less. As described above, recycled materials made of aluminum UBCs have an alloy composition similar to that of 3000 series aluminum alloys, since can bodies made of 3000 series aluminum alloys with low Mg content and high Mn content account for a large proportion of recycled materials. However, even when such recycled materials are used for the ends and tabs of the can lids of the present invention, by using aluminum alloys with the above alloy composition in which the Mg content is adjusted, it is possible to provide can lids that do not have a reduced pressure resistance, and that are free from deformation of the lids and that are effectively prevented from breaking the tabs when opened, even when such recycled materials are used.
[0015] In the aluminum alloy constituting the end and / or tab, the Mn content is preferably in the range of 0.5 to 1.4 mass %, particularly 0.5 to 1.0 mass %. That is, Mn is an essential element for improving the strength of aluminum alloys. However, if the Mn content is too high, the toughness decreases due to an increase in Al-Fe-Mn-Si crystals, which reduces the score strength at the end and may cause the score to break unintentionally. In the case of tabs, there is a risk that the tabs may break or tear when openings are formed, and the repeated bending resistance may decrease. Furthermore, Mg is an essential element for obtaining the strength required for can ends, such as tensile strength, proof stress, and elongation, and if the Mg content is too low, the ends may be deformed when subjected to positive pressure canning or sterilization, and the tab breaking strength may be reduced. Furthermore, if the Mg content is higher than the above range, cracking may occur in the ingot or during hot rolling and can end forming. Therefore, even if the Mn and Mg contents are within the above ranges, if the Mn content is high and Al-Fe-Mn-Si crystals are likely to be abundant, by setting the Mg content to 2.0 to 3.0 mass%, the tensile strength and other properties of the aluminum alloy can be appropriately complemented, and it becomes possible to have excellent pressure resistance while suppressing cracking during forming. On the other hand, in an aluminum alloy with a relatively low Mn content, by setting the Mg content to 3.0 to 4.5 mass%, it becomes possible to similarly have excellent pressure resistance.
[0016] Si and Fe form the Al-Fe-Mn-Si crystals described above, act as recrystallization nuclei during hot rolling, and form crystal grains of various orientations, suppressing concentration in the Cube orientation at the end of hot rolling. From this perspective, the Si content is preferably 0.6% by mass or less, and more preferably 0.35% by mass or less, and the Fe content is preferably 0.8% by mass or less, and more preferably 0.6% by mass or less. Cu and Cr are contained to increase the strength of the aluminum alloy, but if the Cu content is higher than the above range, cracks may occur during hot rolling, and if the Cr content is higher than the above range, coarse intermetallic compounds may be formed. Furthermore, Zn and Ti are impurities that are inevitably contained in aluminum alloys, and if they are below the above-mentioned values, they will not affect the can lid of the present invention.
[0017] Furthermore, in the can lid of the present invention, as described above, by appropriately adjusting the amount of Mg according to the amount of Mn, strength can be ensured by the Mn contained in the recycled material, and as will be described later, by adjusting the remaining score thickness at the initial opening portion of the score-processed portion formed on the end, it is possible to use the can lid without unintended score breakage or tab breakage.
[0018] The aluminum alloy constituting the end and / or tab has the above alloy composition adjusted by adding Mg to a recycled material made of aluminum UBC and, if necessary, adding new aluminum. As mentioned above, the recycled material made of aluminum UBC is mainly made of the 3000 series aluminum alloy that constituted the can body, and therefore contains 0.5 to 1.4 mass% of Mn. In addition to the recycled aluminum UBC, scrap material discharged in the aluminum alloy sheet manufacturing process and the aluminum can manufacturing process can also be used as the recycled aluminum material.
[0019] As described above, the aluminum alloy sheet used for forming the end and / or tab of the can lid of the present invention is produced by melting recycled aluminum, and optionally new aluminum, adjusting the amounts of alloying elements such as Mg, and then hot rolling and cold rolling. It is preferable to perform intermediate annealing during the cold rolling. The aluminum alloy plate may be subjected to various surface treatments as required by conventional methods, and then coated with a thermoplastic resin or an organic coating such as a paint film by conventional methods. Examples of the surface treatment include, but are not limited to, conventionally known surface treatments such as chromate phosphate treatment and chemical conversion treatments containing zirconium and / or titanium oxide as the main component.
[0020] Examples of thermoplastic resin coatings include olefin resin films such as polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic ester copolymer, and ionomer, polyester films such as polyethylene terephthalate, polyamide films such as nylon 6, nylon 6,6, nylon 11, and nylon 12, polyvinyl chloride films, and polyvinylidene chloride films. Such thermoplastic resin films may be unstretched or biaxially stretched. Examples of paints capable of forming a coating film include modified epoxy paints such as phenol-epoxy and amino-epoxy, vinyl chloride-vinyl acetate copolymers, saponified vinyl chloride-vinyl acetate copolymers, vinyl chloride-vinyl acetate-maleic anhydride copolymers, epoxy-modified, epoxyamino-modified, epoxyphenol-modified vinyl paints or modified vinyl paints, acrylic paints, and synthetic rubber-based paints such as styrene-butadiene copolymers.
[0021] The aluminum alloy sheet used for forming the end and / or tab of the can lid of the present invention preferably has a tensile strength in the rolling 0° direction of 350 to 410 MPa, particularly 370 to 400 MPa, in a state where the aluminum alloy sheet is coated and baked with an epoxy-based paint, a polyester-based paint, or the like. When the tensile strength is within the above range, the sheet can also be used as a can lid for a positively pressurized can. The thickness of the aluminum alloy plate is not limited to these values, but the plate thickness as an end material is preferably in the range of 0.19 to 0.30 mm, and the plate thickness as a tab material is preferably in the range of 0.24 to 0.35 mm. In the present invention, it is most preferable that both the end and the tab are made of an aluminum alloy having the above-mentioned composition, and it is preferable that at least the end is made of an aluminum alloy having the above-mentioned composition. Furthermore, the end and the tab do not necessarily have to have the same composition, but it is preferable from the viewpoint of productivity and economy that they are made of an aluminum alloy having the same composition.
[0022] (ends and tabs) The can lid of the present invention is not limited in shape, and various shapes can be adopted as long as it has an end and a tab for breaking a score formed in the end to form an opening. FIG. 1 shows an example of a can lid according to the present invention, where (A) is a plan view and (B) is a cross-sectional view. The can lid, generally designated 1, is a stay-on-tab can lid consisting of an end 2 and a tab 4 fixed to the end 2 with a rivet 3. The end 2 has a circular center panel 21, a chuck wall radius 22 protruding downward from the periphery of the center panel 21, a chuck wall 23 rising from the outer wall of the chuck wall radius 22, and a seaming panel 24 formed continuously with the chuck wall 23. Scores 25 are formed on the center panel 21. The scores 25 consist of main scores 25a and auxiliary scores 25b provided inside the main scores 25a. The auxiliary scores 25b are intended to prevent the main scores from cracking during processing, and do not break shallower than the main scores 25a. On the other hand, the tab 4 comprises a tab main body 41, an arc-shaped tab nose 42 formed at a position on the pouring direction side of the contents, a finger hook (grip) 43 formed on the opposite side of the tab nose 42, and a fixing part 44 to which the tab main body 41 is fixed with a rivet 3. The tab main body 41 is also bent at an outer peripheral edge 45 of the grip part 43, and a curled part 46 folded downward is formed around the entire periphery of the outer peripheral edge other than the grip part 43.
[0023] As described above, in the can lid of the present invention, in order to achieve the pressure resistance and other characteristics required for the end and tab, it is effective to adjust the Mg content of the aluminum alloy constituting the end and tab in accordance with the Mn content. Furthermore, by adjusting the remaining score thickness in the initial opening portion of the score-processed portion formed on the end, it is possible to suppress unintended score rupture and improve openability, thereby effectively preventing the occurrence of tab tearing and other problems. That is, because the initial portion of the scored opening is located directly below the tab, water droplets may adhere to the scored portion. The 5000-series aluminum alloys conventionally used for can ends have a high Mg content, making them highly susceptible to moisture and posing a risk of stress corrosion cracking if the remaining score thickness is reduced. However, aluminum alloys with a Mg content within the above range eliminate the risk of stress corrosion cracking, making it possible to reduce the remaining score thickness in the initial portion of the opening and enabling opening with less force. Meanwhile, aluminum alloys with a high Mn content and a high content of Al-Fe-Mn-Si crystals tend to have poor toughness and are therefore prone to tab tearing during tab opening. However, because opening with less force is now possible, it is possible to effectively prevent tab tearing even in aluminum alloys with a low Mg content.
[0024] Figure 2 is a partial cross-sectional view showing the score formation portion of the end. Specifically, as shown in Figure 2, it is desirable to form the score so that the ratio of the remaining score thickness (thickness of the score processing portion) t1 in the initial opening portion of the score processing portion where the score 25 is formed to the non-processed portion (original plate thickness) t0 of the center panel 21 of end 2 {(t1 / t0) x 100(%)} is 71%. The ratio of the remaining score thickness to the original end thickness t0 varies depending on the original thickness, and the ratio decreases as the original thickness increases. Specifically, within the range of the original end thickness of 0.19mm to 0.30mm, when the original thickness is greater than 0.190mm and less than 0.200mm, the ratio is 71% or less, when the original thickness is greater than 0.200mm and less than 0.210mm, the ratio is 68% or less, when the original thickness is greater than 0.210mm and less than 0.220mm, the ratio is 64% or less, when the original thickness is greater than 0.220mm and less than 0.230mm, the ratio is 61% or less, and when the original thickness is greater than 0.230mm and less than 0.240mm, the ratio is 0. It is preferable that the thickness is 59% or less when the thickness is greater than 230 mm and less than 0.240 mm, 56% or less when the thickness is greater than 0.240 mm and less than 0.250 mm, 54% or less when the thickness is greater than 0.250 mm and less than 0.260 mm, 52% or less when the thickness is greater than 0.260 mm and less than 0.270 mm, 50% or less when the thickness is greater than 0.270 mm and less than 0.280 mm, 48% or less when the thickness is greater than 0.280 mm and less than 0.290 mm, and 47% or less when the thickness is greater than 0.300 mm.
[0025] Furthermore, the auxiliary scores, which are formed together with the breakable main scores and are adjacent to and located inward of the main scores, preferably have a remaining thickness ratio of the main scores in the range of not less than 90% and not more than 90% of the original sheet thickness, and the width thereof is also preferably in the range of 50 to 110 μm. The remaining score thickness and score width do not necessarily have to be the same from the beginning to the end of the score, and can be changed as appropriate depending on the initial opening portion and the position of the score.
[0026] As described above, in the end used in the food and beverage can lid of the present invention, by improving the remaining score thickness and score shape of the breakable score (main score) formed in the end, it is possible to improve the score strength even in an end made of recycled aluminum alloy made from aluminum UBC, which has an increased amount of Al-Fe-Mn-Si based crystallized matter, and as will be described later, it is possible to effectively prevent the occurrence of microcracks in the organic coating on the back surface of the score processing part (inner surface side of the end), derailment when the score breaks, or the so-called pop missile phenomenon when the can is initially opened.
[0027] Score Shape As is clear from FIG. 3, which shows an axial cross section in the width direction of the score, the end of the present invention has opposing inclined surfaces 26a and 26b in at least a part of the main score 25a, the score width of which decreases downward, and a flat surface in the center. Department The inclined surfaces 26a and 26b are continuous with the bottom surface 27 via a curved surface R. Department It is preferable that the width W1 of 27a has at least a portion that is 65% or less of the width W0 of the imaginary bottom surface 27 defined by the imaginary extension lines La, Lb of the inclined surfaces 26a, 26b and the imaginary extension line Lc passing through the center of the bottom surface 27. In this way, the breakable main score has an inclined surface and a bottom surface that are continuous via a curved surface, and the width of the bottom surface (the width of the flat portion 27a in the specific example shown in Figure 2) is formed to be 65% or less of the imaginary bottom surface. This makes it possible to improve the strength of the score, and effectively prevents the score from breaking even when the container is filled with contents and is subjected to impact from being dropped or vibration during transportation. That is, as is clear from the results of the examples described later, the flatter the surface, the better the flatness. Department If the width W1 is too large, there is a risk that the contents may leak from the score. The width of the bottom surface is the distance at the center of the bottom surface excluding the curved surface connecting the inclined surface and the bottom surface. Department If it has a flat DepartmentThe width of the curved surface is as close to zero as possible, and in this case, the bottom surface is substantially arc-shaped and continuous with the curved surface. In addition, in the preferred embodiment of the present invention shown in the figure, the inclined surface and bottom surface of the score are continuous via a curved surface, but even if the inclined surface and bottom surface are not connected via a curved surface, the same effect as when a curved surface is connected may be obtained if the remaining thickness of the score is thick or depending on the angle formed by the inclined surface and bottom surface. In the end of the present invention, the main score has a flat bottom. Department From the viewpoint of improving the strength of the score, it is preferable that the portion where the value is in the above-mentioned numerical range be formed over the entire area of the main score, but it may also be formed partially in a thin portion where the remaining thickness of the score is small, such as the latter half of the opening.
[0028] The width W0 of the imaginary bottom surface of the score bottom is preferably in the range of 15 to 40 μm, which prevents microcracks from occurring in the organic coating (thermoplastic resin coating or paint film) on the inside surface of the score (the back side of the end), effectively prevents metal exposure on the inside surface of the end, and makes it possible to provide an end with excellent corrosion resistance. If the width W0 of the imaginary bottom surface is smaller than the above range, there is a risk of stress corrosion cracking, depending on the material used, while if it is larger than the above range, there is a risk of microcracks occurring on the inner surface of the score portion compared to when it is within the above range.
[0029] Furthermore, the score angle Θ formed by the inclined surfaces 26a, 26b of the score is preferably in the range of 40 to 60 degrees. When the score angle Θ is in the above range, microcracks do not occur in the organic coating on the inner surface of the score (the back side of the end), metal exposure on the inner surface of the end is effectively prevented, and an end with excellent corrosion resistance can be provided. If the score angle is larger than the above range, there is a risk of microcracks occurring in the organic coating on the inside of the score (the back side of the end), and if the score angle is smaller than the above range, there is a risk of damage to the score-forming blade, such as chipping of the cutting edge or chipping or cracking from the base, after long-term use.
[0030] [Metal Rejection Amount of Score] As shown in Fig. 1, the end used in the present invention preferably includes, in addition to the breakable main scores, auxiliary scores adjacent to the main scores and located inward of the main scores. These auxiliary scores are provided to prevent cracking of the main scores during processing and are not breakable themselves, so they have a higher score remaining thickness ratio than the main scores. However, in the present invention, from the viewpoint of preventing microcracks from occurring in the organic coating on the inner surface of the main scores (the inner surface of the end), it is desirable to form the auxiliary scores so that the metal rejection amount S0 due to score processing of the auxiliary scores is 25% or more of the metal rejection amount S1 due to score processing of the main scores in a cross section perpendicular to the width direction of the scores.
[0031] That is, as shown in Figure 4, the cross-sectional areas S0 and S1 of the main score 25a and the auxiliary score 25b in a cross section perpendicular to the width direction are defined as the metal rejection amount, and the main score and the auxiliary score are preferably formed so that the ratio [(S1 / S0) × 100] of the metal rejection amount S1 of the auxiliary score 25b to the metal rejection amount S0 of the main score 25a is 25% or more, particularly in the range of 25 to 200%. If the metal rejection amount of the auxiliary score is smaller than the above range, microcracks may occur in the organic coating on the inner surface of the main score (the inner surface of the end). Furthermore, even if the metal rejection amount exceeds the above range, defects will not occur in the end, but the molding load may increase, posing a risk of breakage to the score-forming tool. The amount of exclusion of the main score and auxiliary score does not need to be constant from the beginning to the end of the score, but may vary depending on the location. The cross-sectional shape of the score does not matter as long as the proportion of the rejected amount is within the above range.
[0032] [High score remaining thickness area] Also, as described above, when the pressure inside the can becomes positive pressure, such as in the case of beer or carbonated beverages, at the initial opening of the score, the opening planned part is rapidly pushed upward by the gas pressure simultaneously with the release of the internal pressure, and the score is broken. Depending on the force, the opening planned part may be separated from the panel part and blown away, resulting in the so-called pop missile phenomenon. By providing a high score remaining thickness part in a part of the main score, such a pop missile phenomenon can be prevented. In the present invention, as shown in FIG. 5 showing the axial cross-section in the score length direction of the main score 25a, a high score remaining thickness part 28 having a larger score remaining thickness than the main score is partially formed in the main score 25a, and it is preferable that the score remaining thickness ratio of this high score remaining thickness part 28 is higher than the score remaining thickness ratio of the main score and 85% or less. That is, as shown in FIG. 5, the score remaining thickness ratio R1 of the main score 25a is the ratio [(t1 / t0)×100(%)] of the main score remaining thickness (t1: the thickness of the score processed part) to the virtual thickness (t0) when the score 25a is not formed. On the other hand, the score remaining thickness ratio R2 of the high score remaining thickness part 28 is represented by the ratio [(t2 / t0)×100(%)] of the remaining thickness (t2) in the high score remaining thickness part. In the present invention, the high score remaining thickness part is formed so that R1<R2≦85%. In addition, as long as the high remaining thickness score part is higher than the score remaining thickness ratio of the main score and 85% or less, the relationship with the main score remaining thickness is not a problem. However, if the step amount from the main score (the remaining thickness difference (t2 - t1) in FIG. 2) is too large, the opening operation will not proceed smoothly and the force required for opening will increase. Therefore, the remaining thickness difference from the main score is preferably 50 μm or less.
[0033] That the score can be smoothly broken without deviating from the line due to the score remaining thickness ratio being within the above range is also clear from the results of the examples described later. That is, when a high score remaining thickness part with a score remaining thickness ratio of 85% or less is formed, even at the end made of an aluminum alloy containing aluminum UBC with a large Mn content and where Al-Fe-Mn-Si-based precipitates tend to increase, the score is smoothly broken without the other parts being broken. On the other hand, if the score remaining thickness ratio of the high score remaining thickness portion is greater than the above range, the breaking of the score may stop at the high score remaining thickness portion 28, and the breaking of the end may deviate from this portion and progress. Furthermore, the length of the high score remaining thickness portion in the score length direction (shown as L in Figure 5) can be changed as appropriate depending on the remaining thickness ratio and formation position of the high score remaining thickness portion, the desired pop missile resistance effect, etc., but it is preferable that it be in the range of 3 to 10 μm.
[0034] Figure 6 is a partially enlarged plan view illustrating the score formed near the tab attachment portion by the rivet 3 in Figure 1. In Figure 6, region A, whose outer edge is indicated by a dotted line, is the coining process region associated with rivet formation, and the sheet thickness in this region is reduced by the coining process compared to other locations. As is clear from Figure 6, main scores 25a and auxiliary scores 25b are formed in coining process region A, and a high score residual thickness portion is formed in main score 25a in coining process region A, and in Figure 6, the high score residual thickness portion is formed from 28a to 28b. The high score residual thickness portion is formed up to position 26b, which is located outside coining process region A, and 28b is a portion where the original sheet thickness of the aluminum alloy plate constituting the end is maintained. In the present invention, the residual thickness ratio of the high score residual thickness portion is based on the virtual thickness that would exist if no score were formed at the location where the high score residual thickness portion is to be formed. Therefore, even when high score residual thickness portions are formed at locations with different virtual thicknesses (t0) as shown in Figure 6, it is possible to form a high score residual thickness portion that is effective for the main score. In other words, the starting point 28a of the high score residual thickness portion may be within or outside region A. The location and number of these high residual thickness score portions are not important, but they are preferably formed in the opening initial portion or around the coining region.
[0035] [Blowout prevention score] Furthermore, as mentioned above, if the contents of the can are beer, carbonated drinks, or the like, and positive pressure is created inside the can, when the score is first opened, the gas pressure will suddenly push the intended opening portion upward as the internal pressure is released, causing the score to break, and depending on the force of the force, the intended opening portion may be separated from the panel portion and blown away, resulting in the so-called pop missile phenomenon. In the end used in the present invention, this pop missile phenomenon can be prevented by forming a score (blowout prevention score) that crosses the auxiliary score near the initial opening portion of the score and is close to the main score, with a remaining score thickness ratio of 70 to 90% of the original plate thickness. That is, the auxiliary score is provided to prevent cracking during processing of the main score and does not break itself. Furthermore, the score extending across the auxiliary score extends in a direction that prevents the progression of breakage of the main score due to the release of internal pressure and the lifting of the intended opening portion, thereby effectively preventing the pop missile phenomenon. If the remaining score thickness of this blowout prevention score is smaller than the above-mentioned range, microcracks may occur in the organic coating on the inner surface of the blowout prevention score (the inner surface of the end). On the other hand, if the remaining thickness ratio of the blowout prevention score is greater than the above-mentioned range, sufficient pop missile resistance cannot be obtained. The anti-ejection score is placed close to the main score and may be placed in a position that does not cross the auxiliary score, i.e., outside the main score. There are no restrictions on the location, but it is preferable to form it in the vicinity of the initial opening portion of the score.
[0036] [rivet] In the end used in the present invention, as will be described later, a rivet is formed in a shell made by press-forming an aluminum alloy plate by rivet forming, and then a tab is fitted into the rivet. After that, the rivet is crimped while pressing the top surface of the rivet, thereby attaching the tab with a rivet. In the end of the present invention, as shown in Figure 7, it is preferable that the thickness at the center of the rivet 30 (i.e., the thickness t3 at the center of the rivet after crimping) is 30% or more of the original plate thickness t0. This effectively prevents the occurrence of microcracks in the organic coating at the center of the top surface of the rivet.
[0037] As described above, in the end to which the tab is attached by crimping the rivet forming portion, as shown in Fig. 8, which is an enlarged cross-sectional photograph of the tab attachment portion, the central region (indicated by diameter D1 in Fig. 8) of the top surface 31 of the rivet forming portion 30 of the end 1, which has been subjected to coining, is thinner than the surrounding area. In the present invention, the ratio of the diameter D1 of this central region to the inner diameter D2 of the side wall portion 32 of the rivet forming portion 30 [(D 1 / D 2 ) × 100] is preferably 40 to 95%, which effectively prevents the occurrence of microcracks in the organic coating at the rivet forming portion. If the proportion of the central region D1 is less than the above range, microcracks may occur in the organic coating in the central region, while if the proportion of the central region is more than the above range, microcracks may occur in the organic coating on the outer edge of the central region D1.
[0038] [tab] In the can lid of the present invention, the tab can be formed from the 5000 series aluminum alloys that have been conventionally used for tabs or the aluminum alloys described above, as described above. In the finger hook portion of the can lid of the present invention, it is preferable that the ratio of the thickness of the finger hook portion to the original plate thickness (thickness of finger hook portion / original plate thickness) is 2 or more and is equal to or less than the ratio of the thickness of the curled portion of the tab to the original plate thickness (thickness of curled portion / original plate thickness). 9(B) shows an example of a tab that can be used in a can lid according to the present invention, with (A) being a plan view and (B) being a cross-sectional view. As shown in Fig. 9(B), the thickness t4 of the finger loop (grip portion) 43 formed by bending and the thickness t5 of the curled portion 46 at the tab nose 42 are such that, relative to the original thickness t0, which is the thickness of the tab material used to form the tab, the ratio (finger loop thickness t4 / original thickness t0) is 2 or more and is equal to or less than the ratio of the thickness of the curled portion of the tab to the original thickness (curled portion thickness t5 / original thickness t0). If the value of t4 / t0 is less than 2, cracks may occur on the metal surface during bending. On the other hand, if the value is greater than t5 / t0, the tab may be misaligned when the rivet forming portion is crimped to attach the tab, preventing the tab from being inserted all the way to the base of the rivet and resulting in defective forming, such as scratches on the rivet.
[0039] (End manufacturing method) The method for manufacturing an end of the present invention is similar to conventional methods for manufacturing an end, except for the use of a specific score-forming blade, which will be described later. Specifically, although not limited to this, a metal plate, such as an aluminum alloy plate, is punched into a circular shape in a press-forming process and formed into a shell shape having the aforementioned seaming panel portion and chuck wall radius portion. A compound is then applied to the grooves in the seaming panel portion in a lining process. Next, a cylindrical rivet projection is formed, and scores are engraved from the outer surface of the end in a score-forming process. Finally, a tab is fitted into the rivet projection, and the head of the rivet projection is crimped to attach the tab, thereby producing an end that can be attached to a can body.
[0040] In the present invention, an important feature is that the score forming blade used in the score forming step in the above-mentioned manufacturing method comprises, in a vertical cross section in the width direction of score forming blade 50, opposing inclined side surfaces 51a, 51b and tip portion 52 located at the lower end of inclined side surfaces 51a, 51b, with the blade width decreasing toward the tip, as shown in Figure 10, and tip portion 52 has, at least in part, a width w1 that is 65% or less of the width W0 of an imaginary tip surface defined by imaginary extension lines La, Lb of inclined side surfaces 51a, 51b and an imaginary extension line Lc passing through the center of tip portion 52. The width of the tip is the distance at the center of the tip excluding the curved surface connecting the inclined side and the tip. Department If it has 52a, it is flat. Department The width of the tip of the stator may be as close to zero as possible, and in such a case, the tip end surface will be substantially arc-shaped and continuous with the curved surface. In addition, in the preferred embodiment shown in Figure 10, both sides of the tip 52 are continuous with the inclined side surfaces 51a, 51b via curved surfaces R, but even if both sides of the tip are not connected to the inclined side surfaces and curved surfaces, the remaining score thickness may be increased, or depending on the angle formed by the inclined side surfaces and the tip, the same effect as when a curved surface is connected may be obtained. By using a score-forming blade having the above characteristics when scoring the end, scores are formed that reflect the characteristics of the score-forming blade as described above, which makes it possible to form scores with improved score strength as described above and also prevents microcracks from occurring on the inner surface of the scoring area.
[0041] 10, the width W0 of the imaginary tip defined by imaginary extension lines La, Lb of inclined side surfaces 51a, 51b of the score-forming blade and imaginary extension line Lc passing through the center of tip 52 of the score-forming blade is preferably in the range of 15 to 40 μm. This prevents microcracks from occurring in the organic coating (thermoplastic resin coating or paint film) on the inside surface of the score (the back side of the end), effectively prevents metal exposure on the inside surface of the end, and makes it possible to form an end with excellent corrosion resistance. If the width W0 of the imaginary tip is smaller than the above range, there is a risk of stress corrosion cracking occurring at the end, depending on the material used. On the other hand, if it is larger than the above range, there is a risk of microcracks occurring on the inner surface of the score compared to when it is within the above range.
[0042] Furthermore, it is preferable that the angle Θ of the score forming blade formed by the inclined side surfaces 51a, 51 of the score forming blade shown in FIG. 10 is 40 to 60 degrees. By setting the angle Θ of the score forming blade within the above range, microcracks do not occur in the organic coating on the inner surface of the score (the back side of the end), metal exposure on the inner surface of the end is effectively prevented, and it is possible to form an end with excellent corrosion resistance. If the angle of the score forming blade is greater than the above range, there is a risk of microcracks occurring in the organic coating on the inside of the score section (the back side of the end), and if the score angle is smaller than the above range, there is a risk of damage to the score forming blade, such as chipping of the cutting edge or chipping or cracking from the base, after long-term use.
[0043] In the rivet forming process, as shown in Fig. 7, after fitting the tab 4 into the shell 2 on which the rivet forming portion 30 has been formed, the tab is attached to the shell with the rivet by the rivet forming process in which the top surface of the rivet forming portion 30 is pressed from above while the rivet forming portion is crimped. In this case, in the present invention, it is preferable to process so that the processing ratio of the original plate thickness at the center of the rivet is 70% or less, particularly in the range of 40 to 70%. Also, as shown in Fig. 8, in the coining process of the rivet top surface portion, the ratio [(D 1 / D 2 ) × 100] is 40 to 95%, which can effectively prevent the occurrence of microcracks in the organic coating at the rivet forming portion. [Example]
[0044] (Experimental Example 1) Aluminum alloy sheets Nos. 1 to 7 having the compositions shown in Table 1, 5182 material, a general-purpose material for end tabs (all of which had been subjected to intermediate annealing during cold rolling, with a thickness of 0.235 mm), and 3104 material, a general-purpose material for can bodies (with a thickness of 0.235 mm), were used to produce 204 diameter shells. Scores were then formed using a scoring tool with a score-forming blade (blade width 35 μm, inclined surface angle 50 degrees), to produce ends. Similarly, tabs having the shape shown in FIG. 9 were made using aluminum alloy sheets Nos. 1 to 7, 5182 material, and 3104 material (each with a thickness of 0.235 mm) having the compositions shown in Table 1, and attached to the ends to make can lids. The obtained can lid was attached to the opening of a seamless can, and 350 ml of beer chilled to 5°C was filled into the can.
[0045] [End and tab molding evaluation] For each end obtained as described above, the surface of the chuck wall radius portion of the end was microscopically observed, and end molding defects were evaluated by marking those with cracks as "x" and those without cracks as "o." The results are shown in Table 1. The surface of the finger loop of each tab obtained as described above was observed under a microscope, and the molding defects of the tab were evaluated by marking those with cracks as "x" and those without cracks as "o." The results are shown in Table 1.
[0046] [Compression strength measurement] A hole was drilled in the body of the beer-filled can obtained as described above, a tube was connected, and air was pumped in at a pressure increase rate of approximately 0.33 kgf / cm per second. 2 The peak pressure was 5.5kgf / cm when the lid turned over. 2 The compressive strength was evaluated by marking the results as "○" if the value was greater than this and "×" if the value was less than this. The results are shown in Table 1.
[0047] [Table 1]
[0048] (Experimental Example 2) A 204 mm diameter shell was prepared from an aluminum alloy plate S (Mn: 0.9 mass%, Mg: 2.3 mass%, Si: 0.3 mass%, Fe: 0.5 mass%, Cu: 0.2 mass%, Cr: 0.01 mass%, Zn: 0.14 mass%, Ti: 0.01 mass%) having a thickness of 0.235 mm. A score was formed on the obtained shell in the usual manner, and a tab was attached to prepare a can lid. The can lid obtained above was attached to the opening of a seamless can, and 350 ml of beer chilled to 5°C was filled into the can.
[0049] [Vibration test] Beer-filled cans having the score remaining rate at the initial opening shown in Table 2 were subjected to a vibration test under the following conditions using a vibration tester (dynamic vibration tester manufactured by Shinken Co., Ltd.). Vibration direction: can axial direction, vibration frequency: 10Hz, vibration time: 60 minutes, amplitude: 5mm, stack number: 24 cans at 3c / s, can temperature: 30℃, internal pressure: approx. 300kPa Those that did not leak from the scored area were evaluated as "◯", and those that leaked were evaluated as "×".
[0050] [Inverted drop test] Beer-filled cans with the score retention rate in the thinnest wall shown in Table 3 were dropped end-side down from a height of 150 cm at a can temperature of 30°C and an internal pressure of approximately 300 kPa, and checked for leakage of beer from the score. Cans that did not leak were rated as "○", and cans that leaked were rated as "×".
[0051] [Opening test] The beer-filled cans shown in Tables 2 and 3 were subjected to opening formation, and those that opened normally were evaluated as "○", and those that did not open normally (failed to open initially, derailed, or only opened partway, etc.) were evaluated as "×".
[0052] [Table 2]
[0053] [Table 3]
[0054] (Experimental Example 3) Main scores were formed on the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 and the 204 diameter shell made of 5182 material with a plate thickness of 0.235 mm using a score processing tool with W0 values shown in Figure 3 and Table 4. The ratio of the flat part to the cutting edge bottom surface (cutting width) was 65%. The surface of the backside of the main score section of the end was checked under a microscope to see if there were any microcracks in the organic coating. Table 4 shows that there were no microcracks and indicates that there were no microcracks, with an "O" and an "X" indicating that there were microcracks. A can lid with a tab attached to the end after scoring was attached to the opening of a seamless can, and 350 ml of beer cooled to 5°C was filled in. The cans were then stored in an environment of 37°C and 80% RH for two weeks. Cans that did not leak were marked with an "O" (good) and were therefore resistant to stress corrosion cracking, while cans that leaked were marked with an "X" (poor) and were therefore resistant to stress corrosion cracking. These are shown in Table 4.
[0055] [Table 4]
[0056] (Experimental Example 4) Main scores were formed on the 204 diameter shell obtained in Experimental Example 2 using a scoring tool with the score angle Θ shown in Figure 3 and the values shown in Table 5. The ratio of the flat portion to the bottom surface (edge width) of the cutting edge was 65%. The surface of the backside of the main score section of the end was checked under a microscope to see if there were any microcracks in the organic coating. Table 5 shows that there were no microcracks and indicates that there were no microcracks.
[0057] [Table 5]
[0058] (Experimental Example 5) Main scores and auxiliary scores having the respective displacements shown in Table 6 were formed in the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 using a score processing tool. In addition, tabs made of 5000 series aluminum alloy plate (5182 material) were attached to form can lids. The surface of the backside of the main score section of the end was checked under a microscope to see if there were any microcracks in the organic coating. Table 6 shows that there were no microcracks and indicates that there were no microcracks, with an "O" and an "X" indicating that there were microcracks.
[0059] [Table 6]
[0060] (Experimental Example 6) Auxiliary scores and main scores (score survival rate 50%) for preventing blowout were formed on the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2, with the score survival rate shown in Table 7. In addition, tabs made of 5000 series aluminum alloy plate (5182 material) were attached to produce can lids. To evaluate the pop missile resistance of the resulting can lid, the can lid was attached to a seamless can, a hole was drilled in the can body, a tube was connected, and air was applied at a pressure increase rate of approximately 0.33 kgf / cm per second. 2 Pressurize to 5.5kgf / cm while checking the pressure gauge value. 2 Internal pressure was applied until the pressure reached 100 psi. The container was opened in this state to check whether it would open normally. Cases where no pop missiles occurred were marked with an "O" and cases where pop missiles occurred were marked with an "X". The results are shown in Table 7.
[0061] [Table 7]
[0062] (Experimental Example 7) The 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 was rivet-formed using a press molding machine so that the working ratio of the rivet top surface was the value shown in Table 8. The presence or absence of microcracks in the organic coating at the center of the rivet top surface was confirmed by microscopic observation. Table 8 shows that there were no microcracks and indicates that there were microcracks with an "O" and an "X".
[0063] [Table 8]
[0064] (Experimental Example 8) Regarding the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2, the D shown in Fig. 8 1 / D 2 The lid was formed using a tool designed to set the values of the ratios shown in Table 9. The organic coating at the center of the D1 region and the outer edge of the D1 region in Figure 8 was confirmed by microscopic observation. Table 9 shows that there were no microcracks and indicates that there were no microcracks.
[0065] [Table 9]
[0066] (Experimental Example 9) Using aluminum alloy sheets S with thicknesses of 0.330 mm and 0.279 mm, tabs with the shape shown in Figure 9 were formed by varying the thickness of the finger loop (grip) while keeping the tab nose thickness constant as shown in Tables 10 and 11. These tabs were attached to the 204 diameter shell (aluminum alloy sheet S) obtained in Experimental Example 1 to create can lids. The presence or absence of microcracks in the organic coating on the tab finger loop was confirmed by microscopic observation. Results were evaluated as "○" when there were no microcracks and "×" when there were microcracks, as shown in Tables 10 and 11. The rivets were also checked for scratches and molding defects. Tables 10 and 11 show that there are no molding defects with an "O" and that there are scratches or other defects with an "X".
[0067] [Table 10]
[0068] [Table 11]
[0069] The content disclosed above is such that anyone who comes into contact with this disclosure can select and use elements as appropriate to obtain benefits corresponding to the selected elements, and can obtain synergistic benefits by combining and using multiple elements. [Industrial Applicability]
[0070] Even when the can lid of the present invention uses recycled aluminum UBC, the amount of alloying elements is adjusted, so that the end has excellent pressure resistance and the tab has excellent fold and tear resistance, and can be used for positive pressure cans. Furthermore, because it is possible to obtain food and beverage can lids similar to those obtained using the new aluminum, the can lid can be suitably used in applications requiring reduced carbon dioxide emissions. Furthermore, by improving the form (shape, dimensions, etc.) of the breakable score (main score) formed in the end, it is possible to provide an end that has high score strength, effectively prevents the occurrence of microcracks in the organic coating, and has excellent corrosion resistance, even in an end made of a recycled aluminum alloy whose raw material is aluminum UBC, in which Al-Fe-Mn-Si-based crystallized matter increases. [Explanation of symbols]
[0071] 1 can lid, 2 end, 3 rivet, 4 tab, 21 center panel, 22 chuck wall radius, 23 chuck wall, 24 seaming panel, 25 score, 26 score inclined surface, 27 score bottom surface, 41 tab body, 42 tab nose portion, 43 grip portion, 44 fixing portion, 46 curl portion.
Claims
1. A method for manufacturing a can lid for food or beverages, the can lid comprising an end and a tab, the end being formed with a breakable score defining an intended opening portion, and the tab being attached by a rivet, comprising: the end and / or the tab are made of an aluminum alloy containing: Mn: 0.5 to 1.4% by mass, Mg: 2.0 to 4.5% by mass, Si: 0.6% by mass or less, Fe: 0.8% by mass or less, Cu: 0.25% by mass or less, Cr: 0.10% by mass or less, Zn: 0.25% by mass or less, and Ti: 0.10% by mass or less; a score forming blade used to form the breakable score, in a vertical cross section in the width direction of the score forming blade, comprising opposing inclined side surfaces whose blade width decreases toward the tip, and a tip portion located at the lower end of the inclined side surfaces, and the width of the tip portion has at least a portion that is 65% or less of the width of an imaginary tip surface defined by an imaginary extension line of the inclined side surfaces and an imaginary extension line passing through the center of the tip portion; A method for manufacturing a lid for food and beverage cans, characterized in that a flat portion is formed in the center of the tip portion, and the width of the flat portion is 65% or less of the width of the imaginary tip surface.
2. 2. The method for manufacturing a can lid for food or beverage according to claim 1, wherein both sides of said tip portion are continuous with said inclined side surfaces by curved surfaces.
3. 2. A method for manufacturing a can lid for food or beverages as described in claim 1, wherein the breakable score has opposing inclined surfaces and a bottom surface in a vertical cross section in the width direction of the score, the score width decreasing downward, and the width of the bottom surface has at least a portion that is 65% or less of the width of an imaginary bottom surface defined by an imaginary extension line of the inclined surfaces and an imaginary extension line passing through the center of the bottom surface.
4. 4. The method for manufacturing a lid for a food or beverage can according to claim 3, wherein a flat portion is formed in the center of the bottom surface, and the width of the flat portion is 65% or less of the width of the imaginary bottom surface.
5. 4. The method for producing a can lid for food and beverages according to claim 3, wherein a width defined by an imaginary extension line of the inclined surface and an imaginary extension line passing through the center of the bottom surface is 15 to 40 μm.
6. 4. The method for manufacturing a can lid for food or beverage according to claim 3, wherein the score angle formed by the inclined surface is 40 to 60 degrees.
7. 3. A method for manufacturing a can lid for food and beverages according to claim 1 or 2, wherein the breakable scores are main scores, auxiliary scores are provided adjacent to the main scores and positioned inwardly of the main scores, and in a cross section perpendicular to the width direction of the scores, a metal rejection amount S0 due to auxiliary score processing is 25% or more of a metal rejection amount S1 due to main score processing.
8. 3. The method for manufacturing a can lid for food and beverages according to claim 1 or 2, wherein the breakable score is a main score, and the main score has a high score remaining thickness portion in which the score remaining thickness relative to the virtual thickness in the case where no score is formed in the score processing portion is greater than the main score remaining thickness ratio and is 85% or less.
9. 3. A method for manufacturing a can lid for food and beverages according to claim 1 or 2, wherein the breakable score is a main score, and an auxiliary score is provided adjacent to the main score and located inward from the main score, an anti-eruption score is formed adjacent to the main score near an initial opening portion of the main score, and a remaining score thickness of the anti-eruption score is 70 to 90% of the original plate thickness.
10. 3. A method for manufacturing a can lid for food and beverages according to claim 1 or 2, wherein a rivet forming portion for attaching a tab is formed in the end, and a processing rate of the rivet forming portion relative to the original plate thickness at the center is 70% or less of the original plate thickness.
11. 3. The method for manufacturing a can lid for food and beverages according to claim 1, wherein a ratio of a coining processing area on a top surface of the rivet forming portion to an inner diameter of a side wall portion of the rivet forming portion of the end is 40 to 95%.
12. 3. A method for manufacturing a can lid for food and beverages as described in claim 1 or 2, wherein, at the finger loop portion of the tab, the ratio of the thickness of the finger loop portion to the original plate thickness (thickness of finger loop portion / original plate thickness) is 2 or more and the ratio of the thickness of the curled portion of the tab to the original plate thickness (thickness of curled portion / original plate thickness) is less than or equal to the value of the ratio.
Citation Information
Patent Citations
Easy oven cover with burtub
JP1981048957A
Sheath-core type composite fiber
JP1983098426A
Pneumatic tire
JP1984020705A
Al alloy sheet for tab having excellent repeated bendability and its manufacture
JP1990149634A
Aluminum lid highly resistant to rupture under high internal pressure
JP1995002248A